Measuring Women Empowerment in Aquaculture – An Empirical Study - De, H. K.; Saha, G. S.; Mahapatra, A. S.; Mohanty, U. L.; Rath, D. P.; Shasani, S.; Sahoo, B.; Panigrahi, A. (Indian Journal of Extension Education, 2023)
Development of index or tool for measuring social parameters has been a key area of research. This research was carried out during the year 2021 for the measurement and quantification of several variables warrants availability of valid tools. In aquaculture sector, gender mainstreaming efforts has been undertaken by several stakeholders. However, measuring the level of empowerment as a consequence of interventions could not be done in absence of such tools. The article describes the process of development of Women Empowerment in Aquaculture Index (WEAI) - selection of domains, assessing content validity through expert rating, screening of the domains using ‘t’ value and assigning relative weights. The instrument, so developed, has 30 items under 6 domains (access to and control over resources and services, ability to decide independently, attitude towards aquaculture, control over use of income, knowledge on aquaculture, participation in social and economic activities). Using the index, comparison was made between three women SHGs from Odisha with level of empowerment varying between 69-80 per cent.
Keywords: Index; Women empowerment; Aquaculture; Women SHG